Validation of protocol for culture-independent detection of Vibrio parachaemolyticus - Escultero, Justine Rose A.
Vibrio parahaemolyticus can cause foodborne illnesses associated with the consumption of raw or partially processed seafoods. The traditional culture method is time-consuming, laborious, and may provide inaccurate detection of this species within seafood sample. Modern molecular techniques have been designed to specifically detect this specific species. It has been reported that the thermolabile hemolysin (tlh) gene is a species-specific marker for V. parahaemolyticus, although its function related to the bacterium's pathogenicity is yet to be determined. In this validation study, a PCR protocol has already been established and a pair of forward and reverse primers was designed based on the tlh gene sequence. The designed primer was then subjected to in-silico analysis for the estimation of its effectivity in detecting the target gene during the actual PCR analysis. Results revealed that non-Vibrio species also matched the designed primers, although all V. parahaemolyticus sequences from the NCBI database matched fully without any single nucleotide mismatch. The in-vitro selectivity test results showed that the protocol is not species-specific (0% selectivity) for it also detected V. cholerae and V. harveyi. The sensitivity test depicted that the established protocol presents a good level of sensitivity and can amplify specific single products at a concentration of at least 102 CFU/mL. Findings of this study show that the use of tlh gene can lead to overestimation of V. parahaemolyticus since this particular gene can also be found in other Vibrio spp.